Recent research progress of circular RNAs in hepatocellular carcinoma - Li, Zhi-di; Li, Yang-ling; Lu, Jing; Liang, Shang; Zhang, Chong; Zeng, Ling-hui (Frontiers in Oncology, 2024)
Hepatocellular carcinoma (HCC) is an extremely heterogeneous malignant tumor with a high morbidity and mortality. Circular RNAs (circRNAs) are noncoding RNAs with high stability, organ/tissue/cell-specific expression and are conserved across species. Accumulating evidence suggested that circRNAs play crucial roles as microRNA sponges, protein sponges, scaffolds, recruiters and could even polypeptide encoders. Many studies have since revealed that circRNAs were aberrantly expressed in HCC and acted as crucial modulators of HCC carcinogenesis and progression. Furthermore, circRNAs have also been identified as potential diagnostic and prognostic biomarkers for HCC. In this review, we thoroughly outline and evaluate the function of circRNAs in HCC development, with an emphasis on the specific molecular pathways by which they participated in the formation and progression of HCC, and we address their potential for serving as clinical biomarkers in HCC.